Differentiating True and False Schematic Memories in Older Adults - Webb, Christina E (J Gerontol B Psychol Sci Soc Sci, 2019)
OBJECTIVE: While schemas aid memory for schematically related information, the gist induced by the schema can also lead to high rates of false memories, especially in older adults. The neural mechanisms that support and differentiate true and false memories in aging are not well understood. The current study sought to clarify this, using a novel scene paradigm to investigate the role of schemas on true and false memories in older adults. METHODS: Healthy older adults encoded schematic scenes (e.g., bathroom). At retrieval, participants were tested on their memory for both schematic and nonschematic targets and lures while functional magnetic resonance imaging data was collected. RESULTS: Results indicate that true memories were supported by the typical retrieval network, and activity in this network was greater for true than false memories. Schema specific retrieval was supported by medial prefrontal cortex, extending this common finding to aging. While no region differentiated false memories compared to correct rejections, results showed that individual differences in false memory rates were associated with variability in neural activity. DISCUSSION: The findings underscore the importance of elucidating the neural basis of cognition within older adults, as well as the specific contribution of individual differences to the neural basis of memory errors in aging.